A sensitivity study of the Navier–Stokes-α model. (15th January 2018) - Breckling, Sean; Neda, Monika; Pahlevani, Fran
Abstract: We present a sensitivity study of the Navier Stokes- α model with respect to perturbations of the differential filter length α . The parameter-sensitivity is evaluated using the sensitivity equations method. Once formulated, the sensitivity equations are discretized and computed alongside the NS α model using the same finite elements in space, and Crank–Nicolson in time. We provide a complete stability analysis of the scheme, along with the results of several benchmark problems in both 2D and 3D. We further demonstrate a practical technique to utilize sensitivity calculations to determine the reliability of the NS α model in problem-specific settings. Lastly, we investigate the sensitivity and reliability of important functionals of the velocity and pressure solutions.